Intra-household insurance and the intergenerational transmission of income risk - Francesco Agostinelli; Domenico Ferraro; Xincheng Qiu; Giuseppe Sorrenti (Tinbergen Institute, 2024)
This paper studies the mechanisms and the extent to which parental wage risk passes through to children's skill development. Through a quantitative dynamic labor supply model in which two parents choose whether to work short or long hours or not work at all, time spent with children, and child-related expenditures, we find that income risk impacts skill accumulation, permanently lowering children's skill levels. To the extent that making up for cognitive skill losses during childhood is hard-as available evidence suggests-uninsurable income risk can negatively impact the labor market prospects of future generations.
Keywords: D1; J13; J22; 330; Wage risk; Household labor supply; Child development; Social insurance